Gerenciamento de resíduos sólidos da Associação Folclórica Boi-Bumbá Garantido pós festival folclórico - Souza, Gabriel Brandão de (Brasil, 2025)
The Parintins Folklore Festival is a cultural event of national repercussion organized and carried out by the Garantido and Caprichoso oxen. The party is held every year, always on the last three days of June, in the city of Parintins, Amazonas, Brazil. P arallel to the celebration, the challenges of building the arena bull are complex and permeate the city's socioeconomic reality. Therefore, after the events of the 2024 Folklore Festival and the need to describe the destination of solid waste after the party, the question arises: How is solid waste from warehouses, produced by the Boi-Bumbá Garantido Folklore Association, managed? Thus, the objective of this study aims to describe the management of solid waste at AFBBG after the edition of the Parintins Folklore Festival (edition nº 57/2024). The research also brings an important and updated academic theoretical framework for the discussion of the topic as it condenses, in a single text, possibilities and risks of environmentally inappropriate disposal of waste to the environment and to the workers of the Folkloric Association. Its social contribution mainly includes the possibility of offering direct and indirect jobs to workers before, during and after the festive period, in a context of stimulating the local creative economy based on management and environmental responsibility initiatives. Methodologically, it is designed as a case study with a qualitative and descriptive approach. The results indicate the Association's concern in generating environmentally appropriate disposal of solid waste, however, the alternatives are still minimal compared to the large amount of waste stored in the period without functional purpose after the Parintins folk festival.